2013
DOI: 10.1074/jbc.m112.438192
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-bound Thyroid Hormone Receptor Contributes to Reprogramming of Pancreatic Acinar Cells into Insulin-producing Cells

Abstract: Background: One goal of diabetic regenerative medicine is to convert mature pancreatic acinar cells into insulin-producing cells. Results: Ligand-bound thyroid hormone receptor ␣ (TR␣), which interacts with p85␣, induces phosphatidylinositol 3-kinase (PI3K) signaling and insulin expression. Conclusion: PI3K signaling must be activated for TR␣-induced reprogramming of pancreatic acinar cells. Significance: TR␣ is critical for postnatal expansion of the ␤-cell mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 39 publications
(41 reference statements)
0
23
0
Order By: Relevance
“…Thyroid hormone effects on glucose homeostasis and on endocrine function of the pancreas are the result of an interaction of the thyroid hormone with its receptors. Recently, we also reported that liganded TR␣ induced expansion of the ␤-cell mass after streptozotocin-induced ␤-cell loss by an increase in the ␤-cell replication and reprogramming of pancreatic acinar cells (12). In this study, long term exposure to oxidative stress enhanced cell death of pancreatic ␤-cells when the expression of endogenous TR␣ was extinguished.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Thyroid hormone effects on glucose homeostasis and on endocrine function of the pancreas are the result of an interaction of the thyroid hormone with its receptors. Recently, we also reported that liganded TR␣ induced expansion of the ␤-cell mass after streptozotocin-induced ␤-cell loss by an increase in the ␤-cell replication and reprogramming of pancreatic acinar cells (12). In this study, long term exposure to oxidative stress enhanced cell death of pancreatic ␤-cells when the expression of endogenous TR␣ was extinguished.…”
Section: Discussionmentioning
confidence: 65%
“…Analyses of Reactive Oxygen Species (ROS) and ApoptosisBy Ficoll gradient centrifugation, the endocrine fraction was prepared from 4-week-old mice (12). Subsequently, the pancreatic ␤-cells were cultured for 6 h on 35-mm culture dishes with RPMI 1640 Gluta MAX-I medium supplemented with 10% resin-stripped FBS at 37°C under 5% CO 2 atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…Dor and co-workers suggested that new β-cells can only be generated from preexisting β-cells instead of MSCs and concluded that MSCs only served as a Btropic mediator^to support islet function in an indirect manner, such as promoting angiogenesis [64]. However, some reports did show that IPCs can be regenerated from the transdifferentiation of other cells, pancreatic duct cells, and acinar cells [65][66][67].…”
Section: Mesenchymal Stem Cells In Treatment Of Diabetes Mellitus Typementioning
confidence: 94%
“…A recent study exploited the role of ligand-bound thyroid hormone receptor  (TR) in expansion of -cell mass during postnatal development (28). Adenovirus-mediated expression of TR in pancreatic acinar cells activated -cell-specific transcription factors such as Hnf6, Foxa2, Nkx2.2, NeuroD1, Pdx1, Ngn3, and MafA when stimulated by thyroid hormone (28).…”
Section: Modulation Of Gene Expression By Ectopic Expression Of Transmentioning
confidence: 99%
“…A recent study exploited the role of ligand-bound thyroid hormone receptor  (TR) in expansion of -cell mass during postnatal development (28). Adenovirus-mediated expression of TR in pancreatic acinar cells activated -cell-specific transcription factors such as Hnf6, Foxa2, Nkx2.2, NeuroD1, Pdx1, Ngn3, and MafA when stimulated by thyroid hormone (28). These results suggest that identification of cell-specific markers within the endocrine system may be exploited to modulate gene expression by small-molecule compounds that drive direct reprogramming to insulin producing cells.…”
Section: Modulation Of Gene Expression By Ectopic Expression Of Transmentioning
confidence: 99%